A polyelectrolyte multilayer platform for investigating growth factor delivery modes in human liver cultures. Issue 4 (4th December 2017) - Lin, Christine; Romero, Raimundo; Sorokina, Lioudmila V.; Ballinger, Kimberly R.; Place, Laura W.; Kipper, Matt J.; Khetani, Salman R.
Abstract: Polyelectrolyte multilayers (PEMs) of chitosan and heparin are useful for mimicking growth factor (GF) binding to extracellular matrix (ECM) as in vivo . Here, we developed a PEM platform for delivering bound/adsorbed GFs to monocultures of primary human hepatocytes (PHHs) and PHH/non‐parenchymal cell (NPC) co‐cultures, which are useful for drug development and regenerative medicine. The effects of ECM protein coating (collagen I, fibronectin, and Matrigel®) and terminal PEM layer on PHH attachment/functions were determined. Then, heparin‐terminated/fibronectin‐coated PEMs were used to deliver varying concentrations of an adsorbed model GF, transforming growth factor β (TGFβ), to PHH monocultures while using soluble TGFβ delivery via culture medium as the conventional control. Soluble TGFβ delivery caused a severe, monotonic, and sustained downregulation of all PHH functions measured (albumin and urea secretions, cytochrome‐P450 2A6 and 3A4 enzyme activities), whereas adsorbed TGFβ delivery caused transient upregulation of 3 out of 4 functions. Finally, functionally stable co‐cultures of PHHs and 3T3‐J2 murine embryonic fibroblasts were created on the heparin‐terminated/fibronectin‐coated PEMs modified with adsorbed TGFβ to elucidate similarities and differences in functional response relative to the monocultures. In conclusion, chitosan‐heparin PEMs constitute a robust platform for investigating the effects of GF delivery modes on PHH monocultures and PHH/NPC co‐cultures. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 971–984, 2018.